Can prebiotic systems survive in the wild? An interference chemistry approach - Walton, Craig R.; Rimmer, Paul; Shorttle, Oliver (Frontiers in Earth Science, 2022)
It is challenging to evaluate the relevance of any given chemical system or geological environment to the origin of life. At the same time, life is the product of prebiotic chemistry that took place in some environment. We may attempt to quantify the probability landscape of organic systems and their host environments on prebiotic worlds as a preliminary step to solving the origin of life. Mapping out the environments and chemical systems of prebiotic habitable worlds requires an integration of at least two fields: prebiotic chemistry, which can discover relevant systems of reactions; and geosciences, which can identify likely planetary environments in which prebiotic systems can develop. However, parallel exploration of prebiotic environmental conditions and chemical systems is inefficient given the immense parameter space available. Here, we propose to emphasize the combined experimental study of prebiotic systems and their proposed host environments, which we term interference chemistry. Environmental variables may interfere either constructively, neutrally, or destructively with specific pathways of organic chemical synthesis, as tracked by e.g., yields or rates of reactions. In turn, prebiotic chemical systems may modify the wider environment, e.g., bulk solution chemistry. Interference chemistry therefore offers an efficient way to construct, describe, and discover prebiotic environmental scenarios, which should in turn assist us assess plausibility for origin of life scenarios.